Outcome after proton beam therapy versus photon-based radiation therapy in childhood-onset craniopharyngioma patients—results of KRANIOPHARYNGEOM 2007 - Friedrich, Carsten; Boekhoff, Svenja; Bischoff, Martin; Beckhaus, Julia; Sowithayasakul, Panjarat; Calaminus, Gabriele; Eveslage, Maria; Valentini, Chiara; Bison, Brigitte; Harrabi, Semi B.; Krause, Mechthild; Timmermann, Beate; et al. (Frontiers in Oncology, 2023)
Background: Proton beam therapy (PBT) is being increasingly used to treat residual craniopharyngioma (CP) after hypothalamus-sparing surgery. Comparing to photon-based radiation therapy (XRT) with PBT, less irradiation penumbra reduces the scattered dose to critical organs neighboring but outside the area of treatment minimizing the risk of sequelae.Patients and methods: Between 2007 and 2019, 99 of 290 (34%) childhood-onset CP patients recruited in KRANIOPHARYNGEOM 2007 received external radiation therapy (RT) (65% PBT, 35% XRT).Outcome was analyzed in terms of survival, endocrinological and anthropometric parameters (BMI and height SDS), quality of life (QoL using PEDQOL) and functional capacity (FMH) with special regard to irradiation technique.Results: PBT became predominant (used in 43% and 72% of all irradiated patients registered within the first and second half of recruitment period, between 2008-2013 and 2013-2018, respectively). 5-year event-free survival rates after PBT or XRT were comparable (92%±4% vs 91%±4%, p=0.42) and higher than for the whole cohort since diagnosis including non-RT patients (37%±4%). Radiation doses to hypothalamus and pituitary did not differ between PBT and XRT. Endocrine deficits due to disturbances of the hypothalamic-pituitary axis (HPA) were already common before irradiation. During the first 5 years after CP diagnosis/RT, no differences between PBT, XRT and non-RT CP patients concerning functional capacity and anthropometric parameters have been obtained. Only for the PEDQOL domain "physical function", parental-assessed QoL was lower 12 months after PBT vs XRT or non-RT patients.Conclusions: QoL, functional capacity, degree of obesity and endocrinopathy varied over time from diagnosis but by 5 years there was no significant difference between PBT and XRT up front or delayed nor was there any compromise in historic survival rates which remained high >90%. RT of any type is extremely effective at stabilizing disease after hypothalamic sparing surgery. The purported specific benefits of PBT reducing sequalae are not proven in this study where the organ of critical interest is itself diseased, increasing an urgent need to better address and treat the tumor-induced endocrine harm from diagnosis in dedicated pituitary services. Other hypothesized benefits of PBT vs XRT on vascular events and secondary cancers await longer comparison.